2011
DOI: 10.1021/jf1041646
|View full text |Cite
|
Sign up to set email alerts
|

Specific Hydroxy Fatty Acids in Royal Jelly Activate TRPA1

Abstract: This is the first report of TRPA1 activation by fatty acids. Activation of TRPA1 and TRPV1 induces thermogenesis and energy expenditure enhancement. In this study, we searched for novel agonists of TRPA1 and TRPV1 from a nonpungent food, royal jelly (RJ). We measured the activation of human TRPA1 and TRPV1 by RJ extracts and found that the hexane extract contains TRPA1 agonists. The main functional compounds in the hexane extract were trans-10-hydroxy-2-decenoic acid (HDEA) and 10-hydroxydecanoic acid (HDAA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 34 publications
0
56
0
1
Order By: Relevance
“…4), 24% gluconic acid, 22% 10-hydroxydecanoic acid (HDAA), 5% dicarboxylic acids and several other acids. 10-HDA and HDAA are specific components of RJ (Terada, Narukawa, & Watanabe, 2011).…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…4), 24% gluconic acid, 22% 10-hydroxydecanoic acid (HDAA), 5% dicarboxylic acids and several other acids. 10-HDA and HDAA are specific components of RJ (Terada, Narukawa, & Watanabe, 2011).…”
Section: 5mentioning
confidence: 99%
“…The results suggested that 3,10-DDA stimulates maturation and Th1 polarising capability of human MoDCs in vitro, which could be beneficial for anti-tumour and antiviral immune responses. Terada et al (2011) stated that activation of TRPA1 and TRPV1 induces thermogenesis and energy expenditure enhancement. They searched for novel agonists of TRPA1 and TRPV1 from RJ.…”
Section: Functional and Health Promoting Propertiesmentioning
confidence: 99%
“…12) RJ consists of 50-60% (w/w) water, 18% (w/w) proteins, 15% (w/w) carbohydrates, 3-6% (w/w) lipids, and 1.5% (w/w) other compounds such as minerals and vitamins. 13,14) A search for the bioactive compound(s) in RJ recently resulted in the isolation of a 57-kDa protein designated royalactin, which is considered to be the major inducer of queen differentiation in honeybees.…”
Section: (Trpv1) and In Ca2mentioning
confidence: 99%
“…It is a rich source of proteins which are composed of a major royal jelly protein (MRJP) family (Li, Wang, Zhang, & Pan, 2007;Nozaki et al, 2012). In addition, RJ contains a unique hydroxy fatty acid, trans-10-hydroxy-2-decenoic acid (HDA) (Terada, Narukawa, & Watanabe, 2011). Substantial evidence indicated that these bioactive components might have many beneficial effects, including antibacterial, antiinflammatory, antioxidant, immunostimulatory and liver regeneration promoting activities (Fujiwara et al, 1990;Majtán, Kovácová, Bíliková, & Simúth, 2006;Kamakura, Suenobu, & Fukushima, 2001;Ramadan & Al-Ghamdi, 2012).…”
Section: Introductionmentioning
confidence: 99%